GPS Carrier-Phase Time Transfer Using Single-Difference Integer Ambiguity Resolution. (27th January 2008) - Delporte, J.; Mercier, F.; Laurichesse, D.; Galy, O.
Abstract : GPS is widely used for time and frequency transfer. To estimate the clock difference between two ground stations, a single baseline solution can be performed using external products for the modelling of the geometrical effects (constellation ephemeris and station coordinates). The baseline solution relies on a single-difference formulation, using code and phase ionosphere-free measurements. The phase ambiguities are usually adjusted as floating parameters. Such solutions give very good results when modelling hypotheses are consistent between the external solution (e.g., GPS orbits) and the baseline solution. However, the frequency bias in the computed clock is very sensitive to discrepancies in the models, and is only observed thanks to the code measurement, with limitations due to the noise. Here, we propose to solve the integer ambiguities on single-difference phase measurements. The advantage is the complete elimination of the clock drifts observed in floating ambiguities solutions. This formulation allows also a reliable continuous connection between overlapping clock solutions (jumps between such solutions can be completely eliminated). Several time transfer results are analyzed and compared to TWSTFT. The methodology has been extended to a network of stations using integer ambiguities on zero-difference measurements. The corresponding results are given for a few European stations.